Fontes e níveis de selênio on top na dieta de leitões desmamados - Almeida, Jorge Luiz Santos de (2019)
Selenium supplementation can improve the immune system by acting on the antioxidant control and modulation of redox cell homeostasis, becoming an alternative to the use of growth promoters in piglet nutrition. The objective of this study was to evaluate the effect of supplementation with or without complex sources on organic selenium molecules, as well as the level of supplementation in the diet of weanling piglets. Forty weaned piglets at 28 days of the same commercial strain were used, with initial average weight of 6.60 ± 1.06 kg, distributed in a randomized block design (DBC) and evaluated in three phases (I - 28 35 days of age II - from 36 to 45 days of age III - from 46 to 60 days of age). The experimental diets consisted of: Control diet without selenium source addition; Control diet supplemented with additional 0.150 mg / kg selenium yeast; Control diet supplemented with an additional 0.150 mg / kg sodium selenite; Control diet supplemented with 0.300 mg / kg additional selenium yeast; Control diet supplemented with an additional 0.300 mg / kg of sodium selenite. Daily feed intake, daily weight gain and feed conversion were evaluated as well as the incidence of diarrhea, nutrient digestibility, serum gamma glutamyl transferase (GGT), aspartate aminotransferase (AST), immunoglobulin A (IGA), immunoglobulin G levels. (IGG) and creatinine, relative organ weight, bowel morphology and immunohistochemistry. Supplementation of 0.300 mg / kg independent of the source reduced (P <0.05) the daily feed intake of the evaluated animals from 28 to 60 days of age, while sodium selenite supplementation improved feed conversion. Selenium yeast supplementation increased the digestibility coefficient of organic matter. The level of 0.150mg / kg reduced serum GGT concentration at 41 days of age, while serum IGA and creatinine levels increased with the level of 0.300mg / kg at 51 and 60 days of age, regardless of source. villus, duodenal abortion area, and jejunal absorptive area increased with the level of 0.150mg / kg regardless of source, as well as a higher rate of duodenal mitosis. Additional supplementation of 0.150 mg / kg selenium is recommended, regardless of source, with the understanding that an additional level of 0.300 mg / kg may cause deleterious effect on consumption, metabolic changes and intestinal morphology, indicating toxicity.